Irrationality rings! - Experimental evidence on mobile tariff choices - Anne-Kathrin Barth; Julia Graf (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
This paper investigates why consumers choose calling plans that are not always cost-minimizing. Our approach is twofold: we account for general difficulties facing a tariff choice, as well as for biased preferences. We provide evidence from an experiment among German university students and staff, finding that participants are often not aware of their actual consumption. In line with the findings on at-rate biases, respondents systematically overestimate their consumption. On the other hand, they are generally able and willing to detect optimal tariffs. Furthermore, with increasing usage level, consumers' performance improves. However, some participants hold strong preferences for certain tariff forms, seducing them to choose cost-dominated offers. In our setup, we find that respondents prefer tariffs involving subsidies or hire-purchase options for handsets over contracts with buy now options.
Keywords: 330; Behavioral Economics; Mobile phone tariffs; Handset subsidy; Hire-purchase of device